From CagA to CagA: the metamorphoses of the Helicobacter pylori's cytotoxin-associated gene A into the cancer-associated gene A - Covacci, Antonello (Henry Stewart Talks, 2010)
Helicobacter pylori: a chronic pathogen with lifelong association with the host, The cag pathogenicity island encoding the Type IV secretion system and the CagA effector molecule, CagA is translocated into the host cells and is tyrosine-phosphorylated by the c-Src kinase, CagA affects the host cell terminal differentiation program, CagA is associated with tumorigenic conversion acting simultaneously on two major pathways
Updated at 2010/07/15